2009
DOI: 10.1177/1069072709334244
|View full text |Cite
|
Sign up to set email alerts
|

Battered Women’s Process of Leaving

Abstract: This study is a follow-up investigation of the career and life experiences of battered women two years after shelter exit. Using consensual qualitative research, we interviewed 6 women from our original sample of 13 regarding their career and life adjustments and future aspirations. Results indicated that participants generally reported both internal and external barriers to their career goals and were dissatisfied with their current housing. In addition, women typically desired education and career advancemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Several qualitative studies documented the barriers to occupational and educational attainment experienced by domestic abuse survivors (e.g., Brown et al 2009, Chronister et al 2008, and one intervention showed promising results. The Advancing Career Counseling and Employment Support for Survivors of Domestic Violence (ACCESS) program has been found to relate to gains in career search self-efficacy and critical consciousness beliefs (Chronister & McWhirter 2006, Davidson et al 2012) and reductions in career barriers, anxiety, and depression (Davidson et al 2012).…”
Section: Promoting Work Participation Of Survivors Of Domestic Violenmentioning
confidence: 99%
“…Several qualitative studies documented the barriers to occupational and educational attainment experienced by domestic abuse survivors (e.g., Brown et al 2009, Chronister et al 2008, and one intervention showed promising results. The Advancing Career Counseling and Employment Support for Survivors of Domestic Violence (ACCESS) program has been found to relate to gains in career search self-efficacy and critical consciousness beliefs (Chronister & McWhirter 2006, Davidson et al 2012) and reductions in career barriers, anxiety, and depression (Davidson et al 2012).…”
Section: Promoting Work Participation Of Survivors Of Domestic Violenmentioning
confidence: 99%
“…However, in research using consensual qualitative research (CQR) protocols (Hill, 2012), racially diverse participants reported an overall distrust of local law enforcement and viewed housing and employment as a means to independent living (C. Brown et al 2005). Additionally, IPV survivors expressed a desire to establish an independent career with a strong overall interest in health care (C. Brown et al 2005Brown et al , 2009. Further, work was seen by some participants as a safe place, although it paradoxically functioned as a source of conflict in abusive relationships (Wettersten et al, 2004).…”
Section: Women In the Workforcementioning
confidence: 99%
“…Specifically, this would address the unique stressors women face because of their identities, such as cultural expectations, systemic racism, discrimination, or marginalization in the workforce (Gomez et al, 2001;House, 2004). For example, female-dominated professions were viewed by some with marginalized identities as "safer" than traditionally male-dominated occupations, where others viewed these occupations as a way to give back (C. Brown et al, 2009;2012). As such, trainees in career counseling might think about assessing the role of a particular career interest and its cohesion with environmental reinforcers when working with women from minoritized backgrounds (see also Lyons et al, 2014).…”
Section: Implications For Trainingmentioning
confidence: 99%
See 2 more Smart Citations